2022
DOI: 10.34198/ejms.8222.295304
|View full text |Cite
|
Sign up to set email alerts
|

The Performance of Redescending M-Estimators when Outliers are in Two Dimensional Space

Abstract: M-estimators are robust estimators that give less weight to the observations that are outliers while redescending M-estimators are those estimators that are built such that extreme outliers are completely rejected. In this paper, redescending M-estimators are compared using both the Monte Carlo simulation method and the real life data to ascertain the method that is more efficient and robust when outliers are in both x and y directions. The results from the simulation study and the real life data indicate that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The authors of [9] carried out a statistical comparison for outlier detection using synthetic bases including 10% of modified data. They conducted the Hampel's test [25] and they found that the Quartile method [26] was more efficient for finding outliers, but the both of them are not suitable for big data . The success of such diagnostic devices used in remote regions by untrained healthcare users depends on the development of advanced image and signal processing techniques that make these devices noise-tolerant and provide accurate diagnos-tics without requiring a high-quality infrastructure [10].…”
Section: Introductionmentioning
confidence: 99%
“…The authors of [9] carried out a statistical comparison for outlier detection using synthetic bases including 10% of modified data. They conducted the Hampel's test [25] and they found that the Quartile method [26] was more efficient for finding outliers, but the both of them are not suitable for big data . The success of such diagnostic devices used in remote regions by untrained healthcare users depends on the development of advanced image and signal processing techniques that make these devices noise-tolerant and provide accurate diagnos-tics without requiring a high-quality infrastructure [10].…”
Section: Introductionmentioning
confidence: 99%